Porous graphene composite conductive slurry and preparation method thereof, positive electrode sheet

By using porous graphene composite conductive paste and preparing porous graphene, the problem of easy agglomeration in the preparation process is solved, and the excellent conductivity and long life of porous graphene in lithium-ion batteries are achieved.

CN119742102APending Publication Date: 2025-04-01SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411974355.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

During the preparation process, the sheet layer is prone to irreversible agglomeration, resulting in limited performance of the electrical properties of single-layer graphene in lithium-ion batteries.

Method used

Porous graphene composite conductive paste is used, including 1% to 15% porous graphene, 1% to 15% superconducting carbon black, 1% to 15% multi-walled carbon nanotubes, 1% to 37% dispersant and 60% to 96% organic solvent, and porous graphene is prepared by ultrasonic dispersion, reduction reaction and freeze-drying to avoid agglomeration.

Benefits of technology

It effectively avoids the agglomeration of porous graphene, improves its conductivity and dispersion effect, increases the contact area with the conductive agent, reduces the interface resistance, and improves the conductivity of the composite conductive paste and the conductivity, rate performance and cycle life of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742102A_ABST
    Figure CN119742102A_ABST
Patent Text Reader

Abstract

The present invention provides a porous graphene composite conductive slurry and a preparation method thereof, and a positive electrode sheet. In terms of mass percentage, the powder of the porous graphene composite conductive slurry includes: 1% to 15% porous graphene, 1% to 15% superconducting carbon black, 1% to 15% multi-walled carbon nanotubes, 1% to 37% dispersant, and 60% to 96% organic solvent. The porous graphene used in this application can avoid the problem of its agglomeration, so that not only the porous graphene can exert its excellent conductivity, but also its excellent dispersion effect in the porous graphene composite conductive slurry, and its rich specific surface area can increase its contact area with the conductive agent, reduce the contact resistance between the electrode and the electrolyte, that is, reduce the interface resistance, and improve the conductivity of the composite conductive slurry. In addition, controlling the content of each of the above components within the above range helps to improve the conductivity, rate performance and cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive pastes, and in particular to a porous graphene composite conductive paste and a preparation method thereof, and a positive electrode sheet. Background Art

[0002] Single-layer graphene has extraordinary physical and chemical properties, including a large specific surface area and good mechanical, electrical and thermal properties. The macroscopic structure of graphene is composed of micron-sized, highly conductive graphene sheets overlapped with each other, and has a rich pore structure. The structural characteristics of graphene materials determine the lithium storage behavior of graphene materials. Lithium ions have a high lithium storage capacity in graphene materials, and the rich pore structure also provides a channel with extremely low potential barriers for the entry of electrolyte ions, which can ensure that graphene materials have good power characteristics as lithium-ion battery materials. In the composite conductive slurry, adding graphene materials with a special structure of two-dimensional high specific surface area and excellent electron transmission ability can greatly improve the conductivity of the positive electrode material and effectively improve the diffusion and transmission capacity of lithium ions and electrons. Compared with traditional conductive additives, the advantage of graphene is that the amount added is less and the electrochemical performance is better. However, since graphene sheets are prone to irreversible aggregation during the preparation process, the preparation of single-layer graphene is difficult to carry out, which greatly affects the performance of its excellent electrical properties and limits the application of graphene in the field of lithium-ion batteries. Summary of the invention

[0003] The main purpose of the present invention is to provide a porous graphene composite conductive slurry and a preparation method thereof, and a positive electrode sheet, so as to solve the problem in the prior art that graphene sheets are prone to irreversible agglomeration during the preparation process, resulting in limited electrical performance of single-layer graphene in lithium-ion batteries.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a porous graphene composite conductive slurry is provided, which comprises, by mass percentage, 1% to 15% of porous graphene, 1% to 15% of superconducting carbon black, 1% to 15% of multi-walled carbon nanotubes, 1% to 37% of a dispersant and 60% to 96% of an organic solvent.

[0005] Furthermore, the specific surface area of ​​the porous graphene is 780 to 1500 m 2 / g, preferably 990 to 1200 m 2 / g; and / or the electrical conductivity of the porous graphene is 133 to 180 S / m, preferably 165 to 180 S / m.

[0006] Furthermore, the solid content of the porous graphene composite conductive paste is 3-10%, preferably 5-6.5%; and / or the viscosity of the porous graphene composite conductive paste is 500-10000 Pa·s, preferably 720-1200 Pa·s.

[0007] Furthermore, the dispersant is selected from any one or more of polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol and sodium dodecylbenzene sulfonate.

[0008] Furthermore, the organic solvent is selected from any one or more of N,N-dimethylformamide, N-methylpyrrolidone, isopropanol and dihydrolevoglucose.

[0009] According to another aspect of the present invention, a method for preparing the aforementioned porous graphene composite conductive slurry is provided, and the preparation method comprises: step S1, ultrasonically dispersing a raw material comprising graphene oxide and water to obtain a graphene oxide solution; first mixing a raw material comprising the graphene oxide solution and a reducing agent to obtain a mixed liquid; step S2, second mixing a raw material comprising the mixed liquid and a surfactant to obtain a microbubble aggregate solution; sequentially subjecting the microbubble aggregate solution to a reduction reaction and freeze-drying to obtain porous graphene; step S3, sequentially premixing and grinding a raw material comprising porous graphene, an organic solvent, a dispersant, superconducting carbon black and multi-walled carbon nanotubes to obtain a porous graphene composite conductive slurry.

[0010] Furthermore, in the above step S1, the concentration of the graphene oxide solution is 2 to 8 g / L; and / or, in the mixed solution, the reducing agent is added in the form of a reducing agent solution, and the concentration of the reducing agent solution is 0.05 to 0.15 mol / L; and / or the reducing agent is selected from any one or more of ascorbic acid, hydroiodic acid, sodium hydroxide, hydrazine hydrate, sodium sulfide and sodium borohydride.

[0011] Furthermore, in the above step S2, the surfactant is selected from any one or more of alkyl glycoside, sodium fatty acid, betaine, sodium alkylbenzene sulfonate and sodium alkyl sulfate; in the microbubble aggregate solution, the mass ratio of the surfactant to graphene oxide is 1:10 to 1:1; and / or the temperature of the reduction reaction is 25 to 90°C, and the time of the reduction reaction is 2 to 8 hours.

[0012] Furthermore, in the above step S3, the stirring speed of the premix is ​​500-800 rpm, and the stirring time is 1-2 h; and / or, the grinding temperature is 10-30° C., the grinding linear speed is 3000-7000 rpm, and the grinding time is 2-5 h.

[0013] According to another aspect of the present invention, a positive electrode sheet is provided, comprising a positive electrode current collector and an active coating coated on the surface of the positive electrode current collector, wherein the active coating is obtained by coating an active slurry on the positive electrode current collector and then drying the active slurry, wherein the active slurry comprises a positive electrode active material, a porous graphene composite conductive slurry, a dispersant and a solvent, wherein the porous graphene composite conductive slurry is the above-mentioned porous graphene composite conductive slurry, wherein the resistivity of the positive electrode sheet is 100 to 168 Ω·cm.

[0014] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a porous graphene composite conductive slurry. Furthermore, the positive electrode plate prepared based on the porous graphene composite conductive slurry has the characteristics of low internal resistance of the plate and high conductivity. Applying the technical solution of the present invention, the porous graphene used in this application can avoid the problem of its agglomeration, so that not only the porous graphene can exert its excellent conductivity, but also its excellent dispersion effect in the porous graphene composite conductive slurry, and its rich specific surface area can increase its contact area with the conductive agent, reduce the contact resistance between the electrode and the electrolyte, that is, reduce the interface resistance, and improve the conductivity of the composite conductive slurry. In addition, controlling the content of each of the above components within the above range helps to improve the synergistic effect of each component, thereby obtaining a composite conductive slurry with better uniformity and electrical properties, thereby improving the conductivity, rate performance and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0016] Figure 1 The scanning electron microscope image of the porous graphene obtained in Example 1 is shown;

[0017] Figure 2 The schematic diagram of the porous graphene and microbubble aggregates obtained in Example 1 is shown, wherein a represents the structural schematic diagram of the microbubble aggregates, and b represents the structural schematic diagram of the porous graphene obtained based on this method. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0019] As analyzed in the background technology of this application, in the prior art, graphene sheets are prone to irreversible agglomeration during the preparation process, resulting in limited electrical performance of single-layer graphene in lithium-ion batteries. In order to solve this problem, this application provides a porous graphene composite conductive slurry and a preparation method thereof, and a positive electrode sheet.

[0020] In a typical embodiment of the present application, a porous graphene composite conductive slurry is provided, which comprises, by mass percentage, 1% to 15% of porous graphene, 1% to 15% of superconducting carbon black, 1% to 15% of multi-walled carbon nanotubes, 1% to 37% of a dispersant and 60% to 96% of an organic solvent.

[0021] The porous graphene used in this application can avoid the problem of its agglomeration, so that not only the porous graphene can exert its excellent conductivity, but also its excellent dispersion effect in the porous graphene composite conductive slurry, and its rich specific surface area can increase its contact area with the conductive agent, reduce the contact resistance between the electrode and the electrolyte, that is, reduce the interface resistance, and improve the conductivity of the composite conductive slurry. In addition, controlling the content of each of the above components within the above range helps to improve the synergistic effect of each component, thereby obtaining a composite conductive slurry with better uniformity and electrical properties, thereby improving the conductivity, rate performance and cycle life of the battery.

[0022] In addition, the mass percentage of porous graphene can be 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. Of course, the mass percentage of porous graphene can be any point value within the range of 1% to 15%. Preferably, the mass percentage of porous graphene can be any point value within the range of 1% to 5%. Further, preferably, the mass percentage of porous graphene can be any point value within the range of 1% to 1.5%, which will not be repeated here.

[0023] The mass percentage of superconducting carbon black can be 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. Of course, the mass percentage of porous superconducting carbon black can be any point value within the range of 1% to 15%. Preferably, the mass percentage of porous superconducting carbon black can be any point value within the range of 1% to 10%. Further, preferably, the mass percentage of porous superconducting carbon black can be any point value within the range of 2% to 5%, which will not be repeated here.

[0024] The mass percentage of multi-walled carbon nanotubes can be 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%. Of course, the mass percentage of multi-walled carbon nanotubes can be any point value within the range of 1% to 15%. Preferably, the mass percentage of multi-walled carbon nanotubes can be any point value within the range of 1% to 10%. Further, preferably, the mass percentage of multi-walled carbon nanotubes can be any point value within the range of 1% to 5%, which will not be repeated here.

[0025] The mass percentage of the dispersant can be 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 36% or 37%. Of course, the mass percentage of the dispersant can be any point value within the range of 1% to 37%. Preferably, the mass percentage of the dispersant can be any point value within the range of 1% to 15%. Further, preferably, the mass percentage of the dispersant can be any point value within the range of 2% to 5%, which will not be repeated here.

[0026] The mass percentage of the organic solvent can be 60%, 61%, 62%, 65%, 70%, 75%, 80%, 85%, 90%, 91%, 93%, 95% or 96%. Of course, the mass percentage of the organic solvent can be any point value within the range of 60% to 96%. Preferably, the mass percentage of the organic solvent can be any point value within the range of 80% to 92%. Further, preferably, the mass percentage of the organic solvent can be any point value within the range of 88.5% to 92%, which will not be repeated here.

[0027] In one embodiment of the present application, the specific surface area of ​​the porous graphene is 780 to 1500 m 2 / g, preferably 990 to 1200 m 2 / g; and / or the electrical conductivity of the porous graphene is 133 to 180 S / m, preferably 165 to 180 S / m.

[0028] It is preferred to control the specific surface area and conductivity of the porous graphene within the above range, which is beneficial to provide more conductive paths and to improve the diffusion efficiency of lithium ions in the composite conductive slurry, thereby improving the conductivity of the composite conductive slurry and the cycle stability of the battery.

[0029] In addition, the specific surface area of ​​porous graphene can be 780m 2 / g、800m 2 / g, 850m 2 / g、900m 2 / g, 950m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g or 1500m 2 / g, of course, the specific surface area of ​​porous graphene can be 780-1500m 2 / g, the specific surface area of ​​the porous graphene can be preferably 990 to 1200 m 2 / g, further preferably, the specific surface area of ​​the porous graphene can be 780 to 1200 m 2 Any point value in / g will not be repeated here.

[0030] The electrical conductivity of the porous graphene can be 133S / m, 134S / m, 135S / m, 140S / m, 145S / m, 150S / m, 155S / m, 160S / m, 165S / m, 170S / m, 175S / m or 180S / m. Of course, the electrical conductivity of the porous graphene can be any point value within the range of 133 to 180S / m. Preferably, the electrical conductivity of the porous graphene can be any point value within the range of 165 to 180S / m, which will not be repeated here.

[0031] In one embodiment of the present application, the solid content of the porous graphene composite conductive paste is 3-10%, preferably 5-6.5%; and / or the viscosity of the porous graphene composite conductive paste is 500-10000 Pa·s, preferably 720-1200 Pa·s.

[0032] It is preferred to control the solid content and viscosity of the porous graphene composite conductive slurry within the above range, which is beneficial to improve the feasibility of the above porous graphene composite conductive slurry coating process and improve the coating uniformity of the porous graphene composite conductive slurry on the positive electrode collector, thereby forming a defect-free electrode layer, thereby improving the overall performance of the battery.

[0033] In addition, the solid content of the porous graphene composite conductive paste can be 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. Of course, the solid content of the porous graphene composite conductive paste can be any point value within the range of 3 to 10%. Preferably, the solid content of the porous graphene composite conductive paste can be any point value within the range of 5 to 6.5%, which will not be repeated here.

[0034] The viscosity of the porous graphene composite conductive paste can be 500Pa·s, 600Pa·s, 1000Pa·s, 2000Pa·s, 3000Pa·s, 4000Pa·s, 5000Pa·s, 6000Pa·s, 7000Pa·s, 8000Pa·s, 9000Pa·s or 10000Pa·s. Of course, the viscosity of the porous graphene composite conductive paste can be any point value within the range of 500 to 10000Pa·s. Preferably, the viscosity of the porous graphene composite conductive paste can be any point value within the range of 600 to 1500Pa·s. Further, preferably, the viscosity of the porous graphene composite conductive paste can be any point value within the range of 720 to 1200Pa·s, which will not be repeated here.

[0035] In one embodiment of the present application, the dispersant is selected from any one or more of polyvinyl pyrrolidone, polyvinyl alcohol and sodium dodecylbenzene sulfonate.

[0036] In the present application, the dispersant is mainly used to improve the dispersibility of components such as porous graphene in organic solvents. By controlling the type of the dispersant within the above range, it is beneficial to improve the dispersibility of the composite conductive slurry, thereby helping to improve the overall electrical properties of the battery electrode.

[0037] In one embodiment of the present application, the organic solvent is selected from any one or more of N-methylpyrrolidone, water, ethanol and N,N-dimethylacetamide.

[0038] It is preferred to control the type of organic solvent within the above range. On the one hand, the fluidity of the porous graphene composite conductive slurry is improved. On the other hand, controlling the type of dispersant within the above range improves the dispersibility of the porous graphene composite conductive slurry and improves the adhesion of the positive electrode active material on the current collector, thereby improving the manufacturing yield and performance of the battery.

[0039] In another typical embodiment of the present application, a method for preparing a porous graphene composite conductive slurry is provided, and the preparation method comprises: step S1, ultrasonically dispersing a raw material including graphene oxide and water to obtain a graphene oxide solution; first mixing a raw material including the graphene oxide solution and a reducing agent to obtain a mixed liquid; step S2, second mixing a raw material including the mixed liquid and a surfactant to obtain a microbubble agglomerate solution; sequentially subjecting the microbubble agglomerate solution to a reduction reaction and freeze-drying to obtain porous graphene; step S3, sequentially premixing and grinding raw materials including porous graphene, an organic solvent, a dispersant, superconducting carbon black and multi-walled carbon nanotubes to obtain a porous graphene composite conductive slurry.

[0040] The preparation method of porous graphene composite conductive slurry in the present application preferably uses surfactant as soft template to prepare porous graphene. Under high-speed ultrasonic dispersion, graphene sheets are dispersed around bubbles created by surfactant to form graphene oxide microbubble aggregates. Under thermal induction of the reduction process, when the graphene oxide microbubbles burst, porous graphene with rich and controllable pore structure is left. Thus, the prepared porous graphene has good electrical conductivity and large specific surface area, and will not agglomerate, thereby increasing the contact area between the positive active material and the conductive agent and reducing the interface resistance. Further, the lithium ion battery prepared by the porous graphene composite conductive slurry including the above porous graphene has good electrical conductivity, rate performance and cycle life.

[0041] In one embodiment of the present application, in the above step S1, the concentration of the graphene oxide solution is 2 to 8 g / L; and / or, in the mixed solution, the reducing agent is added in the form of a reducing agent solution, and the concentration of the reducing agent solution is 0.05 to 0.15 mol / L; and / or the reducing agent is selected from any one or more of ascorbic acid, hydroiodic acid, sodium hydroxide, hydrazine hydrate, sodium sulfide and sodium borohydride.

[0042] It is preferred to control the concentration of the graphene oxide solution, the concentration of the reducing agent solution and the type of reducing agent within the above range, which helps the reducing agent to fully induce the rupture of graphene oxide microbubbles, leaving behind porous graphene with rich and controllable pore structure, thereby facilitating the preparation of porous graphene with more uniform pore structure and better electrical conductivity, and further improving the performance of the composite conductive slurry.

[0043] In addition, the concentration of the graphene oxide solution can be 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L. Of course, the concentration of the graphene oxide solution can be any point value within the range of 2 to 8 g / L. Preferably, the concentration of the graphene oxide solution can be any point value within the range of 5 to 8 g / L, which will not be repeated here.

[0044] The concentration of the reducing agent solution can be 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.10mol / L, 0.11mol / L, 0.12mol / L, 0.13mol / L, 0.14mol / L or 0.15mol / L. Of course, the concentration of the reducing agent solution can be any point value within the range of 0.05 to 0.15mol / L. Preferably, the concentration of the reducing agent solution can be any point value within the range of 0.08 to 0.1mol / L, which will not be repeated here.

[0045] In one embodiment of the present application, in the above step S2, the surfactant is selected from any one or more of alkyl glycoside, sodium fatty acid, betaine, sodium alkylbenzene sulfonate and sodium alkyl sulfate; in the microbubble aggregate solution, the mass ratio of the surfactant to graphene oxide is 1:10 to 1:1; and / or the temperature of the reduction reaction is 25 to 90°C, and the time of the reduction reaction is 2 to 8 hours.

[0046] The addition of the above specific types of surfactants is preferred to form microbubble aggregates, and the mass ratio of the surfactant to graphene oxide is preferably controlled within the above range, which is conducive to the formation of more graphene oxide microbubble aggregates. The temperature and time of the reduction reaction are controlled within the above range, so as to make the pore distribution of the prepared porous graphene more uniform and the structure more stable, thereby helping to improve the conductivity of the composite conductive slurry and the cycle life of the lithium ion battery.

[0047] In addition, the mass ratio of the surfactant to graphene oxide can be 1:10, 1:12, 1:5, 1:4, 1:3, 1:2 or 1:1. Of course, the mass ratio of the surfactant to graphene oxide can be any point value within the range of 1:10 to 1:1. Preferably, the mass ratio of the surfactant to graphene oxide can be any point value within the range of 1:10 to 1:5, which will not be repeated here.

[0048] The temperature of the reduction reaction can be 25°C, 26°C, 30°C, 35°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C. Of course, the temperature of the reduction reaction can be any point value within the range of 25 to 90°C. Preferably, the temperature of the reduction reaction can be any point value within the range of 25 to 80°C, which will not be repeated here.

[0049] In addition, the reduction reaction time can be 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, 7h or 8h. Of course, the reduction reaction time can be any point value within 2 to 8h. Preferably, the reduction reaction time can be any point value within 4 to 8h, which will not be repeated here.

[0050] In one embodiment of the present application, in the above step S3, the stirring speed of the premix is ​​500-800 rpm, and the stirring time is 1-2 h; the grinding temperature is 10-30°C, the grinding linear speed is 3000-7000 rpm, and the grinding time is 2-5 h.

[0051] The conditions of premixing and grinding are preferably controlled within the above range, which improves the dispersion uniformity of the composite conductive slurry and further reduces the probability of agglomeration, thereby facilitating the improvement of the conductivity of the composite conductive slurry and further improving the electrochemical performance of the lithium-ion battery.

[0052] In addition, the stirring speed of the premix can be 500rpm, 510rpm, 530rpm, 550rpm, 600rpm, 650rpm, 700rpm or 800rpm. Of course, the stirring speed of the premix can be any point value within the range of 500 to 800rpm. Preferably, the stirring speed of the premix can be any point value within the range of 600 to 800rpm, which will not be repeated here.

[0053] The stirring time can be 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h. Of course, the stirring time can be any point value within 1 to 2h, which will not be repeated here.

[0054] The grinding temperature can be 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 20°C, 25°C or 30°C. Of course, the grinding temperature can be any point value within the range of 10 to 30°C. Preferably, the grinding temperature can be any point value within the range of 15 to 25°C, which will not be repeated here.

[0055] The linear speed of grinding can be 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 5000 rpm, 5500 rpm, 6000 rpm, 6500 rpm or 7000 rpm. Of course, the linear speed of stirring can be any point value within the range of 3000 to 7000 rpm. The preferred linear speed can be any point value within the range of 5000 to 7000 rpm, which will not be repeated here.

[0056] The grinding time can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h. Of course, the grinding time can be any point value within 2 to 5h. Preferably, the grinding time can be any point value within 3 to 5h, which will not be repeated here.

[0057] In another typical embodiment of the present application, a positive electrode sheet is provided, comprising a positive electrode current collector and an active coating coated on the surface of the positive electrode current collector, wherein the active coating is obtained by applying an active slurry to the positive electrode current collector and then drying the active slurry, wherein the active slurry comprises a positive electrode active material, a porous graphene composite conductive slurry, a dispersant and a solvent, and the porous graphene composite conductive slurry is the above-mentioned porous graphene composite conductive slurry, wherein the resistivity of the positive electrode sheet is 100 to 168 Ω·cm.

[0058] The positive electrode sheet prepared by the composite conductive slurry of the present application has a lower resistivity, which is more conducive to improving the conductivity, cycle performance and rate performance of the lithium-ion battery.

[0059] In addition, the resistivity of the positive electrode sheet can be 100Ω·cm, 105Ω·cm, 110Ω·cm, 115Ω·cm, 120Ω·cm, 125Ω·cm, 130Ω·cm, 135Ω·cm, 140Ω·cm, 146Ω·cm, 150Ω·cm, 160Ω·cm or 168Ω·cm. Of course, the resistivity of the positive electrode sheet can be any point value within the range of 100 to 168Ω·cm. Preferably, the resistivity of the positive electrode sheet can be any point value within the range of 100 to 140Ω·cm, which will not be repeated here.

[0060] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0061] Example 1

[0062] 400 g of graphene oxide with a mass concentration of 8 g / L was dispersed in 50 L of deionized water, and ultrasonicated at a frequency of 50 kHz for 45 min to obtain a graphene oxide solution; then 400 g of ascorbic acid with a mass concentration of 0.1 mol / L was added to the graphene oxide solution and mixed evenly to obtain a dispersion A.

[0063] 80 g of alkyl polyglycoside was added to the dispersion A, and then sheared at 2500 r / min for 3 min to uniformly generate microbubbles to form a microbubble aggregate solution (the schematic diagram of the microbubble aggregate is shown in Figure 2 Then adjust the water bath temperature to 80 ° C, so that the above-mentioned microbubble aggregate solution is reduced, react for 4 hours, and then freeze-dry to obtain porous graphene, the scanning electron microscope image of which is shown in FIG. Figure 1 As shown, the schematic diagram is as Figure 2 As shown in b.

[0064] The porous graphene, superconducting carbon black and multi-walled carbon nanotubes are stirred and mixed at a stirring speed of 600 rpm for 2 hours; polyvinylidene fluoride and N-methylpyrrolidone are premixed to obtain a premixed liquid, wherein the mass ratios of porous graphene, superconducting carbon black, multi-walled carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone are 1.5%, 2%, 3%, 5% and 88.5% respectively. The porous graphene mixture is added to the premixed liquid, and after being fully mixed and stirred, it is added to a homogenizing grinding and dispersing machine for fine grinding and dispersion to obtain a composite conductive slurry, which is finely ground and dispersed for 3 hours at a temperature of 20° C. and a linear speed of 5000 rpm to obtain a porous graphene composite conductive slurry, wherein the porous graphene composite conductive slurry has a solid content of 6.5% and a viscosity of 1200 Pa·s.

[0065] Example 2

[0066] The difference from Example 1 is that the mass ratios of porous graphene, superconducting carbon black, multi-walled carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone are 1.2%, 2%, 3%, 3% and 90.8%, respectively, and finally a porous graphene composite conductive slurry is obtained, and the solid content of the porous graphene composite conductive slurry is 5.3% and the viscosity is 850 Pa·s.

[0067] Example 3

[0068] The difference from Example 1 is that the mass ratios of porous graphene, superconducting carbon black, multi-walled carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone are 1%, 2%, 3%, 2% and 92%, respectively, and finally a porous graphene composite conductive slurry is obtained, and the solid content of the porous graphene composite conductive slurry is 5.0% and the viscosity is 720Pa·s.

[0069] Example 4

[0070] The difference from Example 1 is that the dispersant is polyvinyl pyrrolidone, the solvent is N,N-dimethylformamide, and finally a porous graphene composite conductive slurry is obtained.

[0071] Example 5

[0072] The difference from Example 1 is that the molar concentration of the graphene oxide solution is 5 g / L, and a porous graphene composite conductive slurry is finally obtained.

[0073] Example 6

[0074] The difference from Example 1 is that the molar concentration of the graphene oxide solution is 1.5 g / L, and a porous graphene composite conductive slurry is finally obtained.

[0075] Example 7

[0076] The difference from Example 1 is that the molar concentration of ascorbic acid is 0.08 g / L, and a porous graphene composite conductive slurry is finally obtained.

[0077] Example 8

[0078] The difference from Example 1 is that the molar concentration of ascorbic acid is 0.045 g / L, and a porous graphene composite conductive slurry is finally obtained.

[0079] Example 9

[0080] The difference from Example 1 is that the mass ratio of alkyl glycoside to graphene oxide is 1:8, and a porous graphene composite conductive slurry is finally obtained.

[0081] Example 10

[0082] The difference from Example 1 is that the mass ratio of alkyl glycoside to graphene oxide is 1:10, and a porous graphene composite conductive slurry is finally obtained.

[0083] Embodiment 11

[0084] The difference from Example 1 is that the mass ratio of alkyl glycoside to graphene oxide is 1:12, and a porous graphene composite conductive slurry is finally obtained.

[0085] Example 12

[0086] The difference from Example 1 is that the temperature of the reduction reaction is 25° C., the time of the reduction reaction is 8 h, and finally a porous graphene composite conductive slurry is obtained.

[0087] Embodiment 13

[0088] The difference from Example 1 is that the temperature of the reduction reaction is 95° C., and a porous graphene composite conductive slurry is finally obtained.

[0089] Embodiment 14

[0090] The difference from Example 1 is that the stirring speed of the premix is ​​800 rpm, and a porous graphene composite conductive slurry is finally obtained.

[0091] Embodiment 15

[0092] The difference from Example 1 is that the grinding linear speed is 7000 rpm, and finally a porous graphene composite conductive slurry is obtained.

[0093] Performance Test:

[0094] Specific surface area of ​​porous graphene: tested in accordance with GBT 19587-2017 standard;

[0095] Electrical conductivity of porous graphene: tested in accordance with GB / T 11007-2008 standard;

[0096] Viscosity of composite conductive paste: tested in accordance with GB / T 22235-2008 standard;

[0097] Resistance of the positive electrode: The resistance of the electrode is tested by the four-probe method.

[0098] Comparative Example 1

[0099] The difference from Example 1 is that porous graphene is not added to obtain a porous graphene composite conductive slurry.

[0100] Comparative Example 2

[0101] The difference from Example 1 is that the mass ratios of porous graphene, superconducting carbon black, multi-walled carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone are 0.1%, 2%, 3%, 2% and 92.9%, respectively, and finally a porous graphene composite conductive slurry is obtained, and the solid content of the porous graphene composite conductive slurry is 4.9% and the viscosity is 700 Pa·s.

[0102] The specific surface areas and electrical conductivity of the porous graphene in some examples and comparative examples are listed in Table 1.

[0103] The solid content and viscosity of the porous graphene composite conductive slurry in some examples and comparative examples are listed in Table 2.

[0104] The porous graphene composite conductive slurry obtained in the above embodiments and comparative examples was mixed with the positive electrode main material and coated on the current collector to obtain a positive electrode sheet (the resistivity of the positive electrode sheet was tested). The positive electrode sheet was assembled with a graphite system negative electrode sheet, an electrolyte, etc. into a lithium-ion battery. The rate performance was tested at 0.33C, and the cycle performance was tested after 500 cycles. The resistivity of the positive electrode sheet, the capacity at 0.33C, and the capacity retention rate after 200 cycles of 1C step cycles are listed in Table 3.

[0105] Table 1

[0106] Implementation / Comparative Example <![CDATA[Surface area (m 2 / g)]]> Conductivity (S / m) Example 1 1165 180 Example 5 1050 167 Example 6 810 145 Example 7 1180 178 Example 8 780 142 Example 9 1177 177 Example 10 1200 179 Embodiment 11 850 133 Example 12 990 165 Embodiment 13 850 143

[0107] Table 2

[0108] Implementation / Comparative Example Solid content (%) Viscosity (Pa·s) Example 1 6.5 1200 Example 2 5.3 850 Example 3 5.0 720 Example 4 6.3 1170 Embodiment 14 6.3 1090 Embodiment 15 6.4 1123 Comparative Example 1 4.7 630 Comparative Example 2 4.9 700

[0109] Table 3

[0110]

[0111]

[0112] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0113] The porous graphene used in this application can avoid the problem of its agglomeration, so that not only the porous graphene can exert its excellent conductivity, but also its excellent dispersion effect in the porous graphene composite conductive slurry, and its rich specific surface area can increase its contact area with the conductive agent, reduce the contact resistance between the electrode and the electrolyte, that is, reduce the interface resistance, and improve the conductivity of the composite conductive slurry. In addition, controlling the content of each of the above components within the above range helps to improve the synergistic effect of each component, thereby obtaining a composite conductive slurry with better uniformity and electrical properties, thereby improving the conductivity, rate performance and cycle life of the battery.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous graphene composite conductive slurry, characterized in that: Measured in percentage by mass, the porous graphene composite conductive slurry comprises: 1% to 15% of porous graphene, 1% to 15% of superconducting carbon black, 1% to 15% of multi-walled carbon nanotubes, 1% to 37% of a dispersant and 60% to 96% of an organic solvent.

2. The porous graphene composite conductive slurry according to claim 1, characterized in that: The specific surface area of ​​the porous graphene is 780 to 1500 m 2 / g, preferably 990 to 1200 m 2 / g; and / or the electrical conductivity of the porous graphene is 133 to 180 S / m, preferably 165 to 180 S / m.

3. The porous graphene composite conductive slurry according to claim 1 or 2, characterized in that: The solid content of the porous graphene composite conductive paste is 3-10%, preferably 5-6.5%; and / or the viscosity of the porous graphene composite conductive paste is 500-10000 Pa·s, preferably 720-1200 Pa·s.

4. The porous graphene composite conductive paste according to any one of claims 1 to 3, characterized in that: The dispersant is selected from any one or more of polyvinylidene fluoride, polyvinyl pyrrolidone, polyvinyl alcohol and sodium dodecylbenzene sulfonate.

5. The porous graphene composite conductive paste according to any one of claims 1 to 3, characterized in that: The organic solvent is selected from any one or more of N,N-dimethylformamide, N-methylpyrrolidone, isopropanol and dihydro-levulinic acid ketone.

6. A method for preparing the porous graphene composite conductive slurry according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step S1, ultrasonically dispersing a raw material including graphene oxide and water to obtain a graphene oxide solution; first mixing a raw material including the graphene oxide solution and a reducing agent to obtain a mixed solution; Step S2, performing a second mixing of the raw materials including the mixed solution and the surfactant to obtain a microbubble aggregate solution; performing a reduction reaction and freeze drying on the microbubble aggregate solution in sequence to obtain porous graphene; Step S3, premixing and grinding the raw materials including the porous graphene, organic solvent, dispersant, superconducting carbon black and multi-walled carbon nanotubes in sequence to obtain the porous graphene composite conductive slurry.

7. The method for preparing the porous graphene composite conductive slurry according to claim 6, characterized in that: In the step S1, the concentration of the graphene oxide solution is 2 to 8 g / L; and / or, in the mixed solution, the reducing agent is added in the form of a reducing agent solution, and the concentration of the reducing agent solution is 0.05 to 0.15 mol / L; and / or the reducing agent is selected from any one or more of ascorbic acid, hydroiodic acid, sodium hydroxide, hydrazine hydrate, sodium sulfide and sodium borohydride.

8. The method for preparing the porous graphene composite conductive slurry according to claim 6 or 7, characterized in that: In the step S2, the surfactant is selected from any one or more of alkyl glycoside, sodium fatty acid, betaine, sodium alkylbenzene sulfonate and sodium alkyl sulfate; in the microbubble aggregate solution, the mass ratio of the surfactant to the graphene oxide is 1:10 to 1:1; and / or the temperature of the reduction reaction is 25 to 90° C., and the time of the reduction reaction is 2 to 8 hours.

9. The method for preparing the porous graphene composite conductive slurry according to any one of claims 6 to 8, characterized in that: In the step S3, the stirring speed of the premix is ​​500-800 rpm, and the stirring time is 1-2 h; and / or the grinding temperature is 10-30° C., the grinding linear speed is 3000-7000 rpm, and the grinding time is 2-5 h.

10. A positive electrode sheet, comprising a positive electrode current collector and an active coating coated on the surface of the positive electrode current collector, wherein the active coating is obtained by coating an active slurry on the positive electrode current collector and then drying the active slurry, wherein the active slurry comprises a positive electrode active material, a porous graphene composite conductive slurry, a dispersant and a solvent, wherein: The porous graphene composite conductive paste is the porous graphene composite conductive paste according to any one of claims 1 to 5, wherein the resistivity of the positive electrode sheet is 100 to 168 Ω·cm.